Paris. (Paris : Karsten Greve Galerie, 1989)
Albers, Josef ; Andre, Carl ; Beuys, Joseph ; Chamberlain, John ; Cornell, Joseph ; Dubuffet, Jean ; Fautrier, Jean ; Flavin, Dan ; Fontana, Lucio ; Graubner, Gotthard ; Ikemura, Leiko ; Knöller, Paco ; De Kooning, Willem ; Kounellis, Jannis ; LeWitt, Sol ; Manzoni, Piero ; De Maria, Nicola ; Miro, Joan ; Orlopp, Detlef ; Palermo, Blinky ; Picasso, Pablo ; Prangenberg, Norbert ; Reineking, James ; Tinguely, Jean ; Twombly, Cy ; Wols
Paris, Karsten Greve Galerie, Paris, 21. septembre - 30. novembre 1989
boek